Early events in ovarian oncogenesis - Cvetkovic, Dusica (BioMed Central, 2003)
Ovarian cancer represents the most lethal of the gynecological neoplasms. The molecular and genetic events associated with early ovarian oncogenesis are still largely unknown, thus contributing to the lack of reliable biomarkers for disease detection. Since the majority of ovarian tumors are diagnosed at an advanced stage, the availability of early ovarian cancer tissue samples for molecular analyses is very limited. In this review, problems encountered in the study of early ovarian cancer are presented, along with the controversies concerning precursor lesions and stepwise progression towards ovarian malignancy. Experimental modeling in the development of ovarian cancer is also described, as well as genetic and epigenetic alterations associated with early ovarian cancer. Lastly, examples of technological advances in the study of early ovarian cancer are discussed. Hopefully, the increasing knowledge about molecular and genetic events involved in the early stages of ovarian tumorigenesis will provide the basis for management of ovarian cancer in the future.